1997
DOI: 10.1093/bja/78.5.520
|View full text |Cite
|
Sign up to set email alerts
|

Transcranial cytokine gradients in patients requiring intensive care after acute brain injury

Abstract: After acute brain injury there may be increased intracranial production of cytokines, with activation of inflammatory cascades. We have sought to determine if a transcranial cytokine gradient was demonstrable in paired sera of 32 patients requiring intensive care after acute brain injury. The difference between concentrations of IL-1 beta, IL-6, IL-8 and TNF alpha in jugular venous and arterial serum was measured on admission, and at 24, 48 and 96 h after the primary injury. There were no differences in IL-1 b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
88
0
3

Year Published

2000
2000
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 145 publications
(99 citation statements)
references
References 23 publications
(12 reference statements)
8
88
0
3
Order By: Relevance
“…In the study conducted by Kossmann et al (1997), there was no association between mortality and plasma IL-8 concentration. Similar results were published by McKeating et al (1997) who found that plasma IL-8 level was not elevated in patients with TBI. On the contrary, the recent study by Mussack et al (2002) revealed that high IL-8 plasma level after TBI may be correlated with unfavorable neurological outcome.…”
Section: Discussionsupporting
confidence: 90%
“…In the study conducted by Kossmann et al (1997), there was no association between mortality and plasma IL-8 concentration. Similar results were published by McKeating et al (1997) who found that plasma IL-8 level was not elevated in patients with TBI. On the contrary, the recent study by Mussack et al (2002) revealed that high IL-8 plasma level after TBI may be correlated with unfavorable neurological outcome.…”
Section: Discussionsupporting
confidence: 90%
“…Therefore, we conclude that the AJ gradient is a poor gauge of intracerebral cytokine production, as previous studies have also struggled to show a reliable AJ gradient for cytokines known to be expressed after TBI. For example, McKeating et al (1997) could only show an AJ difference for IL6 but not for IL1b, IL8, and tumour necrosis factor, whereas Goodman et al (2008) found no overt AJ differences for IL1b, IL6, IL8, IL10, IL12, and tumour necrosis factor.…”
Section: Compartmentalisation Of Cytokine Productionmentioning
confidence: 90%
“…Central inflammation is often accompanied by the migration of peripheral inflammatory cells into the brain (57,58). After hypoxic injury, up-regulation of the adhesion molecules vascular cell adhesion molecule (VCAM), intercellular adhesion molecule (ICAM), and E-selectin on cerebrovascular endothelial cells can be inhibited by indomethacin (92,93).…”
Section: Discussionmentioning
confidence: 99%